Understanding the link between gut microbiota, dietary intake, and nutritional status in children with autism and typical development - Mendive Dubourdieu, Paula; Guerendiain, Marcela (Frontiers in Nutrition, 2023)
Background: Gut microbiota plays a potential role on human health and different disorders like autism spectrum disorder (ASD). Therefore, we analysed gut bacteria composition in children with ASD and typical development (TD), and its relationship to nutritional status and dietary intake.Methods: A descriptive cross-sectional study was carried out in 3-12-year-old children (ASD=30, TD=28). Dietary intake (applying food frequency questionnaires) and body mass index-for-age (expressed in z-score) were determined. Children were divided into normal weight and excess weight (risk of overweight + overweight + obesity), and ASD group was categorized into gluten and casein free diet (ASD-diet) or no diet (ASD-no diet). Gut bacteria relative abundances were analysed in faecal samples by 16S rRNA sequencing.Children with excess weight had lower Roseburia than normal weight. Fewer Bifidobacterium longum and higher Clostridium glycolicum were found in ASD group compared with TD one. Participants with excess weight and ASD had lower Roseburia and Faecalibacterium prausnitzi, and higher Eubacterium ventriosum and Flavonifactor plautii than the TD group with the same nutritional status. Positive and negative associations were found between the bacteria genus and species, and the intake of dairy, vegetable drinks, cereals with and without gluten, foods source of proteins, fish, foods source of fat, and coconut oil, in unadjusted models and after adjustment for age, diet/no diet, ASD/TD. Conclusion: Significant differences in microbial community composition were found between children with ASD and TD considering their nutritional status and dietary intake.